Electricity consumption and economic growth: Evidence from Cameroon. Issue 11 (2nd November 2017) - Tamba, Jean Gaston; Nsouandélé, Jean Luc; Fopah Lélé, Armand; Sapnken, Flavian Emmanuel
ABSTRACT: This paper analyzes the electricity sector and examines the causal relationship between electricity consumption and economic growth in Cameroon for the period 1971–2013. Stationary tests, the Johansen co-integration test, the vector autoregressive (VAR) model, and the Granger causality test were used as an econometric approach. The results show that: all variables are I(1); there is no co-integration relation between the variables; and there is no causal relationship between electricity consumption and economic growth. Moreover, the results of the Granger causality test confirm the neutrality hypothesis. Despite its enormous hydroelectric potential, Cameroon does not yet meet its energy requirements in the electricity sector. It must, therefore, implement a strong policy of upgrading, producing, distributing, and popularizing electricity, in order to satisfy demand and contribute to economic growth.